Human Values and Antisocial and Criminal Behaviors - Nilton Soares Formiga; Valdiney V. Gouveia (Psicologia, 2005)
The problem of the violence between the youngs has called attention the most diverse theoretical perspectives how much to its explanation. The human values have been one construto that it comes contributing for the prediction of this phenomenon. Seven hundred and ten young, both the gender and ages between 15 and 22 years, had participated of the study, scale of the antisocial and criminal behaviors, questionnaire of the basic values and demographic questions answering. To invest in values that they aim at the individualism can foment a bigger frequency of the desviantes behaviors between the young, already values that to stimulate behavior into social collectivist norms can contribute with diminution of antisocial and criminal behaviors.